Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Kartu Kata Pada Anak Usia 5 -6 Tahun Di Tk Islam Pamastra Kedaung – Pamulang - Auliah, Elzi; Hamidah, Agustin; ., Rizawati (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Improving initial reading skills in children aged 5 - 6 years is important for children because in children's lives it is always related to reading activities, therefore by mastering one aspect of language skills children are trained to be able to recognize letters, read, recognize objects and so on. etc. to improve beginning language skills through reading card media. Based on the researcher's experience, some of the group B children aged 5 - 6 years in the Pramastra Kedaung - Pamulang Islamic Kindergarten have problems with children recognizing letters and reading. Therefore, researchers look for and find solutions to stimulate children to read. The research subjects in group B were 10 children consisting of 7 girls and 3 boys. Researchers used classroom action research methods to improve language skills through kaa card media. This research was carried out in 2 cycles, namely cycle 1 was carried out in the first week while cycle 2 was carried out in the second week. From the research in cycle 1 in the first week, the results in cycle I showed that the ability to recognize letters and read had not developed well so the research was continued in cycle II which was carried out in the second week. The results showed that the ability to recognize letters and read showed better development results. From the results obtained, there is an increase which proves that initial reading activities using word cards as a medium can improve children's reading abilities.